Policies regulating retail environment to reduce tobacco availability: A scoping review - Alebshehy, Raouf; Asif, Zara; Boeckmann, Melanie (Frontiers in Public Health, 2023)
Background In 2005, the World Health Organization Framework Convention on Tobacco Control (WHO FCTC) entered into force. This treaty was developed in response to the global tobacco epidemic, and it includes measures to reduce both demand for and supply of tobacco. The measures related to demand reduction include raising tax, providing cessation services, promoting smoke free public places, banning advertising, and raising awareness. However, there are a limited number of measures for supply reduction, and these mainly include fighting illicit trade, banning sales to minors and providing alternatives to tobacco workers and growers. Unlike regulation of many other goods and services that have been subjected to retail restrictions, there is a lack of resources about restricting tobacco availability through regulation of tobacco retail environment. Considering the potential of retail environment regulations in reducing tobacco supply and consequently reducing tobacco use, this scoping review aims to identify relevant measures. Methods This review examines interventions, policies, and legislations to regulate tobacco retail environment to reduce tobacco availability. This was done by searching the WHO FCTC and its Conference of Parties decisions, a grey literature search including tobacco control databases, a scoping communication with the Focal Points of the 182 WHO FCTC Parties, and a databases search in PubMed, EMBASE, Cochrane Library, Global Health, and Web of Science. Results Themes of measures were identified to reduce tobacco availability by regulating retail environment: four WHO FCTC and twelve non- WHO FCTC measures. Discussion Studies show the effects of regulation of the retail environment in influencing overall tobacco purchases, and there is evidence that having fewer retails reduces the level of impulse purchasing of cigarettes and tobacco goods. The measures covered by WHO FCTC are much more implemented than ones not covered by it. Although not widely implemented, many themes of limiting tobacco availability by regulating tobacco retail environment are available. The adoption of such measures under WHO FCTC decisions would probably increase their implementation by many countries.